PENGARUH PEMBERIAN BUAH PEPAYA TERHADAP KELANCARAN ASI PADA IBU MENYUSUI DI WILAYAH KERJA PUSKESMAS MESKOM KABUPATEN BENGKALIS - Erliana, Erliana; Tanberika, Fajar Sari; Mardiya, Rizka; Yanti, Rifa (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Breastfeeding is the best method of feeding infants. The coverage of exclusive breastfeeding in the Meskom Community Health Center working area is still below the target, this may be due to insufficient breast milk production. Lactagogum is a substance that can increase breast milk production, which is found in papaya. The purpose of this study was to determine the effect of giving papaya on the smooth flow of breast milk in breastfeeding mothers in the Meskom Community Health Center working area. The type of research used in this study is experimental research. The research design is quasi-experimental and the design is a two-group pretest-posttest with control group design. The population is 30 breastfeeding mothers with a sample size of 24 people. Respondents are divided into two groups, 12 respondents in the treatment group and 12 respondents in the control group. The sampling technique uses purposive sampling. Data analysis is bivariate analysis using a paired sample t-test. The amount of breast milk before being given papaya in the intervention group averaged 176.67 cc. Meanwhile, the control group averaged 181.25 cc. The amount of breast milk after being given papaya in the intervention group on the first day was 179.17 cc on average. Meanwhile, the control group averaged 181.25 cc on the first day. There is an effect of giving papaya on the smooth flow of breast milk in breastfeeding mothers (p-value 0.011 < 0.05). Research conclusion: There is an effect of giving papaya fruit on the smooth flow of breast milk in breastfeeding mothers in the Meskom Community Health Center Working Area. The output of the research is a Journal. It is hoped that breastfeeding mothers should regularly consume papaya fruit, because giving papaya fruit to breastfeeding mothers can stimulate the secretion and increase the amount of breast milk production.Keywords: Papaya fruit, Smooth breast milk flow